Effect of exploration depth on microstructural behavior of subsurface soft clayey soil for foundation construction purposes - Onyelowe, Kennedy; Onyia, Michael E.; Onukwugha, Eze; Udeala, Richard; Mohammed, Nura A.; Yakubu, Isa (Penerbit Universiti Kebangsaan Malaysia, 2021)
The geomorphological, microstructural pattern and mineralogical configuration of subsurface soils explored from 1-meter, 3-meter and 7-meter depths have been studied for the purpose of foundation materials suitability. Soils samples are hauled from borrow sites to where they are utilized as foundation materials. In very most cases, this exploration is done at varying depths and soil being an erratic geomaterial change in its important engineering characteristics with depth. This laboratory examination was necessary to establish the microstructural behaviour and pattern of soils when they are explored from different depths. The samples collected from different depths showed to be A-3 soils according to AASHTO classification method and poorly graded according to the USCS. Also varying depth of the soil sample was characterized by a proportional increase in moisture content; this as well applies to the `liquid limit, plastic limit and plasticity index values respectively with an exception in the shrinkage limit, which reduces with increase in depth of soil sample. This can be attributed to the erratic behavior of soil, which makes it change behavior from location to location and from depth to depth, clayey contents changes with depth likewise its desiccation properties. The geomorphology and microstructure of the soils show weaker configuration with increased depth of exploration to 7 meters. This shows that for any foundation purposes, soils at both 3 meter and 7-meter depths require treatment to be suitable for construction purposes. Geo-constructions like compacted earth liner systems, mechanically stabilized earths or backfills, pavement subgrade systems can be constructed with the studied soils but care must be taken to modify the soils to meet the basic design considerations.